Implementation of the Policy of Granting Presidential Approval to the Draft Regulation of Ministers/Heads of Institutions in the Cabinet Secretariat - Tri Eka Sunarti Dewi; Ima Mayasari (Journal of Social Research, 2024)
One of the functions of the Cabinet Secretariat is to conduct assessments and provide recommendations on the policy plans of Ministries/Institutions in the form of Ministerial/Institutional Regulations that need to be approved by the President. To support this function, Presidential Regulation Number 68 of 2021 concerning the Granting of Approval to the Draft Regulation of Ministers/Heads of Institutions has been stipulated. This research was conducted to determine the implementation of the President's policy of granting approval to the Draft Regulation of Ministers/Heads of Institutions in the Cabinet Secretariat. The research method used is qualitative which will present a detailed picture of a situation. Based on the results of the research, the implementation of the policy of granting Presidential approval to the Draft Regulation of Ministers/Heads of Institutions in the Cabinet Secretariat shows that with the enactment of Presidential Regulation Number 68 of 2021, Ministries/Institutions have involved the Cabinet Secretariat in the discussion stage of harmonization of the Draft Regulation of Ministers/Heads of Institutions. With the existence of Presidential Regulation Number 68 of 2021 pressuring Ministries/Institutions to submit applications before establishing Ministerial/Institutional Heads, this needs to be done so that the prepared Ministerial Regulations/Heads of Institutions will also be more in line with the President's policies and directives. However, in its implementation, the policy of granting presidential approval to the draft Regulation of Ministers/Heads of Institutions in the Cabinet Secretariat still has several problems such as the absence of clear sanctions in the implementation of granting approval of the policy plans of Ministries/Institutions in the form of Ministerial/Institutional Regulations. Furthermore, the Standard Operating Procedures (SOP) have not been established. In addition, it is related to the Information System for Monitoring the Draft Regulation of Ministers/Heads of Institutions (Sippermen) which has not been running optimally, because this system is still segmented and not disseminated so that it cannot be accessed by other Ministries/Institutions.